MAKNA SEKOLAH BAGI SISWA DAN ORANGTUA DI SMPN 3 SATU ATAP SUNGAI MANDAU KECAMATAN SUNGAI MANDAU KABUPATEN SIAK - Yusnita " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Schoolis an educational in stitution that is created by government to educate childrenas a step to prepare the child's potentialin order to achieve the country's progress. Meaning of school for students and parentsa place to study and place to wardsa bright future.This study a imed to analyze the meaning of school for students and parents. there are factstostate schools is a form of building that can make the school as the center of attention in the community, the parents and the students who attend school. From the school situation, it appears the various positive and negative assumptionsas of the assessment for students and parents to the school situation. Subjec tsandin for mants here are community leaders, teachers, parents and students. To analyze the data conducted qualitative research, the data were collected and analyzed with descriptive qualitative technique. Descriptive qualitative techniqueis one kind of qualitative research that is used to express the state of education in the school.Researchers in this caseattempted to describe the state of the school sareoccupied by students. This research was conductedin the village Bencah Umbai, from there sults showed that of the views of child renand parentsin understanding schoolas a place of study and the school makes a success ful child. What is meant by the school where study in gis the schoolis an institution designed for the teaching or students under the supervision of teacher education. Most countries have systems of for maleducation, which is generally required, in order to create students in order to progress after going througha learning process. School became one of the for mation of personality and intell ectual development of the child, the school not only as avenue for the learning process, but also the educational process. School is a symbol for the acquisition of know ledge. Actually, that dete rmines the success of a person is not the one school, but the people who go to school, and depend on ourselves. Schoolis aplaceto study and give a good lesson or know ledge, the school can be a place to educate children well are given by the teachers are teachers.Keywords: Meaning of Schools, Students and Parents